Relationships among diurnal variations of polar night cloud, precipitation, surface temperatures, and the fair-weather return current of the global electric circuit (GEC). (March 2023) - Lavigne, Thomas; Liu, Chuntao
Abstract: Over the past five years (June 2017-current), the vertical electric field (Ez ) as well as numerous cloud, precipitation and radiation properties have been monitored at the Department of Energy-Atmospheric Radiation Measurement (DOE ARM) North Slope of Alaska (NSA) field site. Comparisons between the composite diurnal averaged fair-weather Ez, and composite ceilometer derived cloud base height during the polar night, reveal a significant correlation between the parameters (r = 0.62), supporting previous studies that there is high correlation between local electric field and cloud properties. With the use of extensive instrumentation at the site, such as the Micro Pulse Lidar (MPL), Ka-band Zenith Radar (KAZR), ceilometer, SKYRAD, Precipitation Imaging Package (PIP), among others, this study provides a more comprehensive examination of the diurnal cycle of cloud and precipitation properties along with the localized fair-weather return current of the larger Global Electric Circuit (GEC) system. Comparisons between the composite diurnal averaged fair-weather Ez, and cloud thickness, maximum column backscatter, and precipitation particle counts all show similar diurnal variability during the polar night, indicating that during the largest magnitude fair weather Ez time periods, clouds bases tend to be higher, clouds are thicker, have a larger column backscatter, and display more precipitating particles. Furthermore, a slight diurnal variability in the polar night surface temperature was found to be highly correlated (r = 0.87) to the longwave downwelling irradiance measured by SKYRAD, indicating that the variations in the physical properties of local clouds could modulate the diurnal polar night surface temperature variability on the order of 0.5 °C/day. These findings emphasize the importance and global nature of the GEC system, with the global aggregate of thunderstorms and electrified clouds potentially influencing polar night cloud properties as well as diurnal wintertime polar surface temperature variation. Highlights: A significant relationship is found between the CBH in Barrow, AK, and the fair-weather Ez during the polar night. During periods of larger magnitude fair-weather Ez, the clouds tend to be taller, thicker, and precipitate more particles. The fair-weather Ez and the longwave downwelling irradiance from clouds in Barrow are found to be statistically correlated. An even larger correlation is found between the diurnal longwave downwelling irradiance and surface temperature in Barrow.